Assessing the Impact of Work Environment on Employee Engagement among Non-Academic Staff of the University - Yusuf Nasidi; A. U. Makera; A. M. Kamaruddeen; I. M. Jemaku (SEISENSE Journal of Management, 2019)
Aim of the Study - The objective of this study was to access the impact of work environment on employee engagement among the non-academic staffs of the university in Nigeria. Social exchange theory (SET) was utilized in developing the research framework. Methodology - A total of 150 non-academics staff from l University, representing a response rate of 63.3% participated in this study. Data were collected through a self-administered questionnaire. The correlation and the hypothesis were tested using the statistical package for social sciences (SPSS 2.0). The Cronbach’s Alpha value for the variables ranging from 0.724 to 0.804 indicates very good reliability of the research instrument. Findings - The findings indicate a moderate relationship between the work environment and employee engagement, and the hypothesis is not supported. Practical Implications - The study will provide direction to both the management and the university staff for them to proactively focus on providing a healthy and comfortable working environment that will boost engagement, which lead towards enhancing the performance of university staff, and also the university administrators in various ways.